Schwannoma of T12 Vertebra: Case Report and Review of Literature. (2000) - Ramasamy, P.; Shackleford, I.; Al Jafari, M.
Abstract : We report a case of schwannoma of the twelfth thoracic vertebra that presented with paraparesis. The tumour was excised, and posterior and anterior stabilisation was performed. Eighteenmonths following this procedure, the patient has solid bony union, satisfactory neurological improvement and no recurrence.